PELARANGAN RIBA DALAM PERBANKAN; IMPACT PADA TERWUJUDNYA KESEJAHTERAAN DI MASA COVID-19 - Binti Nur Asiyah; Nur Azrin Yuliani; Evita Amelia; Fifin Nasiroh (Imara: JURNAL RISET EKONOMI ISLAM, 2020)
The aim of prohibiting usury is to protect people who conduct mu’amalah. Indeed, Al qur’an prohibited it because it is resulted injustice. It is obviously felt in the period of Covid-19 Pandemic.  The research purpose was to analyze the problems of applying usury system in banking and to analyze the privileges of prohibiting usury system in banking. The descriptive research was used in this paper. The results show usury systems resulted gaps and injustice. Indeed, it is also caused economic instability. A solution for this problem is profit sharing. This system can bring justice and it will lead into economic equality particularly in the era of Covid-19 pandemic. Therefore, by applying Islamic economic system, the economy is more stable and social welfare can be achieved.